Work by app: algorithmic management and working conditions of Uber drivers in Brazil. (1st January 2020) - Amorim, Henrique; Moda, Felipe
Abstract : Aiming to contribute to the understanding of how the relationship between autonomy and control is materialised in 'work by app', this article draws on the results of research conducted in the city of São Paulo, Brazil, with Uber drivers, The research aimed to analyse the management practices in 'app' work. Because this survey was conducted in the global South, we also present some considerations about the Brazilian working-class conformation and the conditions under which work by app is being performed in Brazil. We argue that the algorithmic management made possible by adopting apps across labour processes is consolidating a new form of management, organisation and control of labour power, increasing workers' actual subsumption to capital and radicalising forms of work exploitation and domination.